Environmental functions of the Teknaf Peninsula mangroves of Bangladesh to communicate the values of goods and services - Chowdhury , M.Sh.N.; Hossain , M.S.; Mitra , A.; Barua , P. (Mesopotamian Journal of Marine Sciences, 2022)
Mangroves are highly productive wetland ecosystems and extremely important coastal resources providing a variety of environmental goods and services, which are vital to our socio-economic development. To evaluate the role of mangroves, a total of 75 semi-structured interviews were conducted with coastal community, resource user, government official, NGO personnel, researchers, and private entrepreneur to gather primary and secondary information. Results indicated that in the past 30 years there has been planted about 1,460 ha of euryhaline mangroves under different management regimes. Teknaf peninsula mangrove influenced two key variables viz., productivity and physical structure which direct other ecological processes. The variable ‘productivity’ provide suitable habitat for nursery, growth, migration through recycling waste and nutrients. The respondents identified 13 mangrove resource user groups in Teknaf peninsula which shows high dependency to mangroves goods. The catch of finfishes, shrimps and prawns, crabs, molluscs, etc. from the mangroves area contributes value to the small-scale fisheries. The knowledge gained from the information content of the Teknaf peninsula mangroves ecosystem contributes value to scientific and educational community. In particular, it means that environmental goods and services provided by the Teknaf peninsula mangroves are rarely produced independently and the multiple interdependencies involved in providing such environmental supports.